Lactate Dehydrogenase is involved in but not the Target Antigen in Children with Kawasaki Disease - Lanqing Zhao; Chunna Zhao; Zhongdong Du; Hongwu Du (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
Background: Kawasaki disease (KD) is an acute vasculitis often complicating coronary arterial lesions, and gradually becomes the leading cause of acquired heart disease instead of rheumatism. Previous studies often regards elevation of serum lactate dehydrogenase (LDH) level as an auxiliary diagnosis marker when judging myocardial diseases. Methods: We analyzed the serum LDH levels in newly confirmed KD patients, compared with febrile non-KD patients and healthy donors as controls. Then a subtype of LDH protein (LDHA) were over-expressed and purified for antigenicity analysis of potential anti-LDHA autoantibodies in IgA, IgM and IgG isotype by homemade ELISA, respectively. Results: An obvious elevation serum levels of LDH was found in 5/27 KD patients (19%, p<0.05) and 16/27 febrile non-KD patients (59%, p<0.001). None of IgA or IgM isotype of anti-LDHA antibodies were detected in all cases, and only low titer IgG antibodies were detected in KD patients (7%) and febrile non-KD patients (11%). Conclusions: Our results demonstrated the LDH was associated but not the main autoimmune target in children with KD.